Masgapur sebagai Simbol Toleransi Beragama di Desa Gaprang Kanigoro Blitar - Tohari, Maula Safira Putri; Zahra, Endris Kirana; Muna, Alfina Nailul (Proceedings of Annual Conference for Muslim Scholars, 2024)
This study aims to understand and examine how individuals from different religious backgrounds interact within a pluralistic society. This paper will elaborate on the diversity of the community in Kampung Pancasila, Desa Gaprang, Blitar, and how the attitudes of tolerance and mutual respect have been successfully cultivated among the community members. A qualitative research approach with a field research method was employed in this study. Data was collected through direct on-site observations and interviews with key community figures, including village leaders and religious leaders from Islam, Christianity, and Hinduism in the Masgapur region of Kampung Pancasila, Desa Gaprang, Blitar. The findings of this study reveal that the diversity within the Kampung Pancasila community is met with tolerance, mutual respect, and a sense of care for one another. The community members engage in collaborative efforts and mutual cooperation regardless of their religious affiliations. It was also observed that during religious holidays, representatives from other religions participate in maintaining a conducive atmosphere for the respective religious events. Consequently, a positive acculturation has been achieved, enabling the community to embrace diversity as a natural aspect of society that should be preserved.